Analysis of Lost VAT Revenue from Purchases of Used Clothing (Thrift) in the Lampung Thrift Fest Community - M Firmansyah; Dedy Yuliawan; Heru Wahyudi; Ukhti Ciptawaty (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to analyze how much VAT revenue is lost as a result of purchasing used clothing (thrift) in the Lampung Thrift Festival community. The data collection methods and analysis tools used in this research are questionnaires, interviews and validity tests, reliability tests. The dependent variable used is tax payments and the independent variables used are thrift taxes and consumer behavior. The best sampling technique obtained was Non-Probability Sampling. The results of the research show the sales of 20 used clothing traders, the behavior of used clothing consumers, potential missing VAT data, missing sales and VAT data for a total of 3 months.